Role of Cultural Intelligence and Customer Involvement on Behavioral Loyalty Toward Manufactured Products in Nigeria - Vem, Linus Jonathan; Eshue, Patrick Ojei; Ramayah, Thurasamy (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2024)
Evidence from the literature reveals that customer loyalty research is growing and is becoming more widely integrated into related disciplines. This study evaluates the role of sales representatives’ cultural intelligence (CI) in the behavioral loyalty (BL) of customers of SMEs in Nigeria, through the mechanism of customer involvement (CuI). Two sets of questionnaires were administered directly to the sales representatives, and indirectly to the customers, via the sales representatives. Three hundred and fifty copies of the sales representatives’ questionnaire were administered, based on the population of 65 manufacturing SMEs and an average of 5.4 copies per SME, while 384 copies of the customers’ questionnaire were sent to the unknown pool of customers. Data were col- lected from the two sets of respondents, which were analyzed through a variance-based structural equation modeling using Smart-PLS software. The results reveal a positive and significant relationship between cultural intelligence and behavioral loyalty, while the in- direct relationship reveals customer involvement does strongly mediate the relationship between the antecedent and the outcome. The findings imply that behavioral loyalty is engendered when sales representatives possess high cultural intelligence, and customers are strategically involved through consultations and product co-creation.